Th1Th17CM Lymphocyte Subpopulation as a Predictive Biomarker of Disease Activity in Multiple Sclerosis Patients under Dimethyl Fumarate or Fingolimod Treatment - Bibiana Quirant-Sánchez; Silvia Presas-Rodriguez; María José Mansilla; Aina Teniente-Serra; José V. Hervás-García; Luis Brieva; Ester Moral-Torres; Antonio Cano; Elvira Munteis; Juan Navarro-Barriuso; Eva M. Martínez-Cáceres; Cristina Ramo-Tello (Mediators of Inflammation, 2019)
Peripheral blood biomarkers able to predict disease activity in multiple sclerosis (MS) patients have not been identified yet. Here, we analyzed the immune phenotype of T lymphocyte subpopulations in peripheral blood samples from 66 RRMS patients under DMF (n=22) or fingolimod (n=44) treatment, by flow cytometry. A correlation study between the percentage and absolute cell number of each lymphocyte subpopulation with the presence of relapses or new MRI lesions during 12-month follow-up was performed. Patients who had undergone relapses showed at baseline higher percentage of Th1CM cells (relapsed: 11.60±4.17%vs. nonrelapsed: 9.25±3.17%, p<0.05) and Th1Th17CM cells (relapsed: 15.65±6.15%vs. nonrelapsed: 10.14±4.05%, p<0.01) before initiating DMF or fingolimod treatment. Kaplan-Meier analysis revealed that patients with Th1Th17CM (CD4+CCR7+CD45RA-CCR6+CXCR3+) cells>11.48% had a 50% relapse-free survival compared to patients with Th1Th17CMcells<11.48% whose relapse-free survival was 88% (p=0.013, log-rank test). Additionally, a high percentage of Th1Th17CM cells was also found in patients with MRI activity (MRI activity: 14.02±5.87%vs. no MRI activity: 9.82±4.06%, p<0.01). Our results suggest that the percentage of Th1Th17CM lymphocytes at baseline is a predictive biomarker of activity during the first 12 months of treatment, regardless of the treatment.